Arabic Learning Design at Islamic Boarding School Higher Education - Rahmawati, Fitra Awalia; Zarkasyi, Ahmad Hidayatullah; Al-Rochim, Dhafa (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This study aims to describe the design of Arabic language learning in both academic and non-academic settings at Islamic boarding colleges. This research utilizes a qualitative approach with a case study design. Data is collected through interviews, observations, and documentation. The data analysis employs the Miles and Huberman model, which consists of data reduction, display, and verification techniques. The findings of this research indicate that Arabic language learning in the classroom has not yielded maximum results due to various constraints. Therefore, Islamic boarding colleges have ample opportunities to design Arabic language learning inside and outside the classroom. Universitas Darussalam (UNIDA) Gontor, an Islamic boarding college, offers various activities supporting academic and non-academic learning. Out-of-classroom learning complements classroom learning. Arabic language learning outside the classroom is conducted under the auspices of the Directorate of Language Development (DPB) of UNIDA Gontor, in collaboration with the heads of departments at UNIDA Gontor and the Directorate of Pesantren Affairs (DKP) of UNIDA Gontor. Hopefully, this research will serve as a reference for Arabic language learning practices in Islamic boarding colleges.